The role of interpersonal communication in resolving social conflicts in the taman mutiara indah community, serang city - Ikrimatul Amal; Annisa Eka Mardiyah; Dwi Ulina Sari (LEGAL BRIEF, 2025)
The role of interpersonal communication in resolving social conflicts in society, with a focus on how direct interaction between individuals can reduce tension and rebuild harmonious social relationships. The main problem studied is the low effectiveness of conflict resolution due to a lack of openness and empathy in communication between residents. The theories used include interpersonal communication theory (Devito) and conflict resolution theory (Deutsch), which emphasize the importance of empathy, openness, and trust as the basis for effective communication. The research method used is descriptive qualitative with a case study approach in communities that have experienced social conflict. Data were obtained through interviews, observations, and documentation to describe interpersonal communication patterns in the mediation and conflict resolution process. The results of the study indicate that open, honest, and empathetic interpersonal communication can accelerate the peace process, increase mutual understanding, and foster trust between conflicting parties. In conclusion, interpersonal communication has a strategic role as a means of rebuilding social cohesion and strengthening community solidarity in facing conflict, thus becoming an important foundation for creating a peaceful and sustainable social life.